Interaction of CO with Mg-FER: combined experimental and theoretical approach - Voleská, Iva (Univerzita Pardubice, 2009)
This work is focused on the combined experimental and theoretical investigation of CO interaction with zeolite Mg-FER. The infrared spectroscopy was used as an experimental technique for study of vibrational frequency of adsorbed CO molecules on Mg-FER. The calculations of Mg-FER and CO-Mg-FER were performed at the periodic DFT level, and the ?CO/rCO correlation was applied for vibrational frequency calculations. The FTIR spectra were interpreted and discussed with theoretical results.
Studium interakce molekul CO se zeolitem Mg-FER: kombinovaný experimentální a teoretický přístup
Keywords: Adsorption; Mg- ferrierite; carbon monoxide; FTIR spectroscopy; Adsorpce; Mg-ferrierit; oxid uhelnatý; FTIR spektroskopie